Marching towards the Cruzada: Douglas Jerrold's road to nationalist Spain - F. Hale (Acta Theologica)
The Spanish Civil War pitted British Christians against each other in an intense battle for the hearts and minds of the public. Generally speaking, Roman Catholics in the United Kingdom favoured the insurgency of General Francisco Franco, who promised to restore the disestablished Catholic Church to its perch of privilege from which the socialist government had removed it and end the violent anticlericalism which had ravaged religious personnel in Spain. Perhaps no English Catholic played a more central role in the almost daily war of words in the secular and religious press than Douglas Jerrold (1893-1964), a lay publicist, novelist, and amateur historian whose Tory sentiments and disillusionment with liberal democracy and the course of modern civilisation in general permeated his writing. In the present article, which traces Jerrold’s political thought through his fictional and nonfictional work, it is demonstrated that his advocacy of Franco’s Nationalist forces was not merely a knee-jerk response to the anticlericalism of 1936 but virtually an inevitable consequence of his commitment to what he termed the “Counter-Revolution” as a means of restoring his vision of an earlier era.